2022
DOI: 10.3389/fmicb.2022.839513
|View full text |Cite
|
Sign up to set email alerts
|

The Intrapopulation Genetic Diversity of RNA Virus May Influence the Sensitivity of Chlorine Disinfection

Abstract: RNA virus populations are not clonal; rather, they comprise a mutant swarm in which sequences are slightly different from the master sequence. Genetic diversity within a population (intrapopulation genetic diversity) is critical for RNA viruses to survive under environmental stresses. Disinfection has become an important practice in the control of pathogenic viruses; however, the impact of intrapopulation genetic diversity on the sensitivity of disinfection, defined as –log10 (postdisinfected infectious titer/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Several mechanisms via which virus populations adapt to disinfection have been reported. The responses of virus populations, including rotavirus, echovirus 11, coxsackievirus B5, MS2 coliphage, and MNV to exposure to various disinfectants, such as chlorine dioxide, ultraviolet radiation, calcium hydroxide, and ozone, have been investigated ( Carratalà et al, 2017 ; Zhong et al, 2017a , b ; Torii et al, 2021 ; Kadoya et al, 2022 ; Oishi et al, 2022 ). A study found that MNV populations exhibited lower susceptibility to calcium hydroxide due to a specific mutation in the VP1 protein, which causes the substitution of lysine at position 345 with arginine ( Oishi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several mechanisms via which virus populations adapt to disinfection have been reported. The responses of virus populations, including rotavirus, echovirus 11, coxsackievirus B5, MS2 coliphage, and MNV to exposure to various disinfectants, such as chlorine dioxide, ultraviolet radiation, calcium hydroxide, and ozone, have been investigated ( Carratalà et al, 2017 ; Zhong et al, 2017a , b ; Torii et al, 2021 ; Kadoya et al, 2022 ; Oishi et al, 2022 ). A study found that MNV populations exhibited lower susceptibility to calcium hydroxide due to a specific mutation in the VP1 protein, which causes the substitution of lysine at position 345 with arginine ( Oishi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The entire serial passage experiment of MNV was performed in duplicate (rounds 1 and 2) for each population to assess the reproducibility of the responses to chlorine ( Figure 1 ). Furthermore, as the susceptibility of the RNA virus population to disinfectants may differ, the virus population in each passage was analyzed separately for the first and second rounds ( Rachmadi et al, 2018 ; Kadoya et al, 2022 ; Oishi et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations